Victims, survivors and the emergence of 'endurers' as a reflection of shifting goals in the management of redeployment. (10th August 2020) - McLachlan, Christopher J.; MacKenzie, Robert; Greenwood, Ian
Abstract: The victim and survivor debate conceptualises employees impacted by restructuring as one or the other. A key contribution of this study is the identification of a conceptually distinct category of employee impacted by restructuring, the endurer . Endurers are survivors who share many of the experiences of victims, occupying a space in‐between the two and not easily understood as either. Endurers experience redundancy of role yet retention of employment. This creates specific needs that pose new challenges for the human resource (HR) function. Through examining the HR function's implementation of an internal redeployment strategy at SteelCo, the study reveals the displacement of substantive goals by institutional goals, and the impact this has on endurers. The analysis of endurers' experiences also offers a conceptual lens for understanding changes to the psychological contract in the context of restructuring.